2018
DOI: 10.1038/s41588-018-0088-x
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory variants at KLF14 influence type 2 diabetes risk via a female-specific effect on adipocyte size and body composition

Abstract: Individual risk of type 2 diabetes (T2D) is modified by perturbations of adipose mass, distribution and function. To investigate mechanisms responsible, we explored the molecular, cellular, and whole-body effects of T2D-associated alleles near KLF14. We show that KLF14 diabetes-risk alleles act in adipose tissue to reduce KLF14 expression, and modulate, in trans, expression of 385 genes. We demonstrate that, in human cellular studies, reduced KLF14 expression increases pre-adipocyte proliferation but disrupts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
161
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 69 publications
13
161
0
Order By: Relevance
“…Variants at 19 signals displayed larger effects in females with the most differentiated signals at CMIP (rs2925979, female OR=1.09, male OR=1.03, p het =8.3x10 -6 ), KLF14 (rs1562396, female OR=1.09, male OR=1.04, p het =0.00048), and MAP3K11 (rs1783541, female OR=1.10, male OR=1.04], p het =0.00058). The female-specific effects on T2D risk at KLF14 15 are consistent with those previously-reported for lipids16 and, given evidence that the risk variant acts as a regulator of KLF14 expression in adipose tissue, indicate sexually-dimorphic effects on fat deposition. At the other 12 signals, larger effects were seen in males, with the differentiation most marked at ANK1 (rs4736819, female OR=1.03, male OR=1.09, p het =0.00021).…”
Section: Resultssupporting
confidence: 88%
“…Variants at 19 signals displayed larger effects in females with the most differentiated signals at CMIP (rs2925979, female OR=1.09, male OR=1.03, p het =8.3x10 -6 ), KLF14 (rs1562396, female OR=1.09, male OR=1.04, p het =0.00048), and MAP3K11 (rs1783541, female OR=1.10, male OR=1.04], p het =0.00058). The female-specific effects on T2D risk at KLF14 15 are consistent with those previously-reported for lipids16 and, given evidence that the risk variant acts as a regulator of KLF14 expression in adipose tissue, indicate sexually-dimorphic effects on fat deposition. At the other 12 signals, larger effects were seen in males, with the differentiation most marked at ANK1 (rs4736819, female OR=1.03, male OR=1.09, p het =0.00021).…”
Section: Resultssupporting
confidence: 88%
“…Do carriers of the risk allele also have increased risk of other phenotypes associated with type 2 diabetes? Through integration with other GWAS, risk alleles at this locus were also found to be associated with increased fasting insulin, decreased high‐density lipoprotein cholesterol, and increased triglycerides . Finally, does modulation of the expression of KLF14 impact risk for type 2 diabetes?…”
Section: A Causal Pathway By Which Genetic Variation Impacts Risk Forsupporting
confidence: 58%
“…Which gene(s) might this regulatory element regulate? Again, when genotypes, methylation of the DNA, and gene expression were acquired from a large sample of genetically diverse human tissue samples, the risk allele for type 2 diabetes was associated with increased methylation at the enhancer region and decreased expression of the closest gene, KLF14 , specifically in adipose tissue . Do carriers of the risk allele exhibit altered morphology of adipocytes?…”
Section: A Causal Pathway By Which Genetic Variation Impacts Risk Formentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, by using a sex‐stratified re‐analysis of the genome‐wide association study (GWAS) data from the GWA meta‐analyses, Kerrin S et al, found that females had substantially higher KLF14 expression and larger effect sizes, as compared with males. To further explore drivers of the sexual dimorphism in KLF14 expression, Kerrin S et al, compared KLF14 expression between pre‐menopausal and postmenopausal females . They failed to identify the correlation between KLF14 and sex hormone.…”
Section: Structure and Characteristics Of Klf14mentioning
confidence: 99%